sebuah Karakterisasi dan Pembuatan Half Cell SOFC Berbasis Ni-YSz dengan Menggunakan NiO Lokal - Retno Dwi Jayanti; Riniati Riniati; Della Agustia Marhani; Chyntia Wahyuni Febryanti; Lina Troskialina (Fluida, 2025)
Indonesia has great potential to produce Nickel Oxide due to the abundance of Ni resources that can be used for the manufacture of SOFC anode components. Ni-YSZ which is a mixture of metal and ceramic is widely used SOFC anodes. Ni was selected because it exhibits high electrical conductivity and serves as an internal reforming catalyst. In this study, the characterization and manufacturing of Ni-YSZ-based half cells using domestic NiO were conducted. The stages of half cell fabrication begin with the mixing of solid and liquid materials and, the process of milling, sonication, degassing, tape casting, and sintering. The manufacture of half cells was carried out by adding an anti-foam concentration with a variation of 0.4; 0,6; and 0.8%. The optimal percentage composition was 0.4% anti-foam variation with a visual appearance that was not cracked, slightly curved and posed a pore size of 0.779 μm. The results of the domestic NiO characterization of imported NiO showed greater element percentage values and viscosity values, a slightly curved half cell visual appearance, good electrolyte density, and porosity values that were not in accordance with the range.